A IDENTIDADE CULTURAL DOS INDÍGENAS NA OBRA METADE CARA, METADE MÁSCARA, DE ELIANE POTIGUARA - DIAS, Eveline Gonçalves (2023)
This research aimed to analyze the cultural identity of the indigenous people in the literary work Metade Cara, Metade Máscara (2004), by Eliane Potiguara. As theoretical support, we build on the literary scholarship of Graça Graúna (2013), Eliane Potiguara (2004), Daniel Munduruku (2011), Stuart Hall (2014), Gayatri Spivak (2010), Zygmunt Bauman (2005), Homi Bhabha (2005), Aníbal Quijano (1992), Joël Candau (2011) among others. The methodology used is qualitative, analytical and bibliographic. From this perspective, the initial chapter is based on indigenous literary manifestations in Brazil, taking into account the confluence of voices in contemporary times and the perceptions of indigenous literature as a movement of resistance. The second chapter discusses the epistemological implications of postcolonial discourse and contemporary identity issues. Thus, during the course of the study, some questions attest: the deconstruction of negative stereotypes in relation to the Amerindians, the diasporic process as a reflection of the colonizers' actions and their consequences, the rescue of the traditions and customs of the Potiguara peoples as a form of resistance to the cultural impositions and identity affirmation, as emphacized in the referred novel. In this way, this study presents discussions relevant to post-colonial and identity studies, pointing out the ambivalence in the composition of the circumscribed narrative from the indigenous ancestral memory of the mentioned writer. The third chapter brings an analysis of the cultural identity of the indigenous people through the narrative Metade Cara, Metade Máscara (2004). As a result, it is possible to perceive the contribution and effort of indigenous writers in contemporary literary productions to reframe historically annulled voices. Potiguara’s novel dialogues, permanently, with history, with memory, with the cultural plurality of the Brazilian and Amerindian peoples, with the codes of non-canonical written tradition, with information technologies and with technological media, in a constant process of refutation to resignify the identities marked, socially and historically, by the diasporas of the original peoples in Brazilian territory and its developments.